Counteracting effects of nutrient composition (Si:N) on export flux under artificial upwelling - Baumann, Moritz; Goldenberg, Silvan Urs; Taucher, Jan; Fernández-Méndez, Mar; Ortiz, Joaquin; Haussmann, Jacqueline; Riebesell, Ulf (Frontiers in Marine Science, 2023)
To keep global warming below 1.5°C, technologies that remove carbon from the atmosphere will be needed. Ocean artificial upwelling of nutrient-rich water stimulates primary productivity and could enhance the biological carbon pump for natural CO2 removal. Its potential may depend on the Si availability in the upwelled water, which regulates the abundance of diatoms that are key carbon exporters. In a mesocosm experiment, we tested the effect of nutrient composition (Si relative to N) in artificially upwelled waters on export quantity and quality in a subtropical oligotrophic environment. Upwelling led to a doubling of exported particulate matter and increased C:N ratios to well beyond Redfield (9.5 to 11.1). High Si availability stimulated this carbon over-consumption further, resulting in a temporary ~5-fold increase in POC export and ~30% increase in C:N ratios compared to Si-scarce upwelling. Whilst the biogenic Si ballast of the export flux increased more than 3.5-fold over the Si:N gradient, these heavier particles did not sink faster. On the contrary, sinking velocity decreased considerably under high Si:N, most likely due to reduced particle size. Respiration rates remained similar across all treatments indicating that biogenic Si did not protect particles against microbial degradation. Si availability thus influenced key processes of the biological carbon pump in counteracting ways by increasing the export magnitude and associated C:N ratios but decreasing the efficiency of carbon transfer to depth. These opposing effects need to be considered when evaluating the potential of artificial upwelling as negative emission technology.